Necrotizing sialometaplasia: report of a self-limiting lesion with malignant appearance - Loureiro, Caio Cesar de Souza; Souza Junior, Alberi Jose Thomas de; Dutra, Mateus Jose [UNESP]; Anbinder, Ana Lia [UNESP] (Univ Republica, Fac Odontologia, 2024)
We report a case of a 45-year-old man with a palate ulcer for 10 days. The patient was an alcohol user and had a history of using cocaine for 17 years, discontinued for the last 7 years. An incisional biopsy was performed, and histological sections revealed an extensive ulcerated area covered by a fibrinopurulent membrane, with small nests of squamous cells in the connective tissue. These squamous cells exhibited eosinophilic cytoplasm, evident and sometimes multiple nuclei, mild cellular atypia, and several mitotic figures. The clinical and histological characteristics indicated a Necrotizing Sialometaplasia diagnosis, and the patient underwent clinical follow-up. In the third week of follow-up, remission of the lesion became apparent. We emphasize the importance of histopathological and immunohistochemical examination in the correct diagnosis.
Keywords: Necrotizing sialometaplasia; Salivary gland neoplasms; Squamous Cell Carcinoma of Head and Neck; Oral ulcer